A Systematic Literature Review (SLR): Implementation of the Traditional Rubber Throwing Game in Science Learning on Adaptation of Living Creatures - Luthfiah, Siti Zubaidah (S&Co Publishing, 2024)
In the material on the adaptation of living creatures, several problems were found during the learning process. Previous researchers saw that during the learning process regarding the adaptation of living things, some students were less active and did not pay attention, because the teacher only used textbooks as media. The learning model used is observational, so that learning is less meaningful and makes students less motivated to study material on the adaptation of living things. This research aims to provide recommendations to teachers for creating interesting and fun learning by applying the traditional rubber throwing game to the material on adaptations of living creatures. The method used in this research is the Systematic Literature Review (SLR) method using the Google Scholar database. The results of research conducted by 3 previous researchers showed that the traditional game of throwing rubber can increase students' understanding and improve student learning outcomes. The rubber throwing game can be said to have succeeded in improving student learning outcomes seen from the student learning completion diagram and the class average score.